A market-based mechanism as an alternative solution for watershed management: a case study of the Ciliwung Watershed, Indonesia. (12th September 2019) - Saridewi, Tri Ratna; Fauzi, Akhmad
The complexity of managing the Ciliwung Watershed in Indonesia has resulted in various externalities such as flooding in the capital city of Jakarta. A non-structural approach using a market-based instrument such as a payment for environmental services (PES) scheme could be considered an alternative policy to overcome such externalities. A compensation mechanism is expected to induce incentives to conserve the watershed in the upstream area with the goal of reducing flooding downstream. This study attempts to determine the amount of compensation that should be paid by the governmental agency in Jakarta to upstream communities to maintain and improve the quality of the watershed area. The contingent valuation method (CVM) was used to obtain the households' willingness to pay (WTP) as a basis for compensation. Lessons learned concern watershed management and the implications of using the PES scheme.